Protective Effects of Anwulignan against HCl/Ethanol-Induced Acute Gastric Ulcer in Mice. (15th July 2021) - Liu, Jiawei; Lin, Huijiao; Yuan, Liwei; Wang, Dan; Wang, Chunmei; Sun, Jinghui; Zhang, Chengyi; Chen, Jianguang; Li, He; Jing, Shu
Abstract : Gastric ulcer is one of the most common gastrointestinal diseases. Anwulignan (AN) is a major active component of Schisandra sphenanthera Rehd . This study was designed to evaluate the protective effect of AN against the acute gastric ulcer induced by HCl/ethanol in mice. The mice were given HCl/ethanol by gavage to establish an acute gastric ulcer model. Then, the serum and gastric tissue samples were taken for biochemical analyses. The results showed that the pretreatment with AN could significantly reduce the gastric ulcer index (GUI) and increase the ulcer inhibition rate, indicating that AN can protect against gastric ulcers. AN showed its antioxidant roles by decreasing the content of reactive oxygen species (ROS), malondialdehyde (MDA), and 8-hydroxydeoxyguanosine (8-OHdG) and increasing the activity of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) and anti-inflammatory roles by decreasing the content of tumor necrosis factor- α (TNF- α ), interleukin-6 (IL-6), interleukin-1 β (IL-1 β ), and myeloperoxidase (MPO) and increasing the content of interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-10 (IL-10), prostaglandin E2 (PGE2), and nitric oxide (NO) in both serum and gastric tissue. Furthermore, AN also activated the NRF2/ARE signaling pathway and inhibited the MAPK/NF- κ B signaling pathway. AN improves the acute gastric ulcer induced by HCl/ethanol in mice, which may be mainly through its antioxidant capacity and anti-inflammatory effect.